Critical analysis of the guandu river basin preservation through sustainable methodologies in combating the burning of solid waste - Felício Marinho da Silva, Geórgia; Luiz Fernandes de Amorim, André; Almeida , Josimar (Seven Editora, 2023)
Given the socioeconomic and environmental importance of the Guandu River in relation to the municipalities of the State of Rio de Janeiro, as well as its respective basin, the propagation of sustainable methodologies for its preservation becomes essential and indispensable for the continuous improvement of sustainable development and, consequently, of the quality of life of its population. Therefore, the present research shows methodologies that could be used in its surroundings, with the potential to provide the reduction or elimination of the practice of burning waste, promoting a Circular Economy, according to the principles predisposed in the Life Cycle Assessment. Works carried out by the company Ciclo Orgânico and the cooperative Coopideal were reported, which denote an excellent waste management, with the development of methodologies for selective collection, composting and recycling, enabling the increase in environmental awareness, social integration, source of income, providing vegetation composites, supporting the carbon footprint and maintaining a sustainable society. In addition, laboratory research was carried out in order to demonstrate a new way of managing organic waste, related to the use of biodigesters, making a 5.5 L benchtop (batch), having inside an elutriate of processed foods, added to waste of swine, in a ratio of 1:2 at the end of 30 days, there was a 70% methane contingent under ideal production conditions within 28 days and an amount of biofertilizer equivalent to the water ratio present in the biodigester, which is also an alternative source of income and enables the improvement of soil and flora quality. DOI: https://doi.org/10.56238/tfisdwv1-140